The Impact of Monetary and Macroprudential Policies on Inflation and Unemployment with the Role of Green Credit in Indonesia - Nadyne Ira Arsyanda; Rusiadi Rusiadi; Wahyu Indah Sari (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the influence of monetary and macroprudential policies on inflation and unemployment in Indonesia using green credit as an intervening variable. This study uses Indonesian time-series data for the 2015-2024 period sourced from Bank Indonesia, the Financial Services Authority, and the Central Statistics Agency. The analysis method used is the Two Stage Least Square (2SLS) simultaneous equation model due to the reciprocal relationship between inflation and unemployment. The estimation results indicate that monetary and macroprudential policies have a direction of influence that is consistent with macroeconomic theory, although not yet statistically significant. The gross domestic product variable plays a role in reducing inflationary pressures, while green credit shows potential in suppressing unemployment and structural inflation in the long term. These findings indicate the importance of integrating monetary policy, macroprudential policy, and green financing to maintain macroeconomic stability and support the transition to a sustainable economy in Indonesia.